sj-docx-1-dhj-10.1177_20552076231225084 - Supplemental material for Toward telemedical diagnostics—clinical evaluation of a robotic examination system for emergency patients ... - Berlet, Maximilian; Fuchtmann, Jonas; Krumpholz, Roman; Naceri, Abdeldjallil; Macari, Daniela; Jähne-Schon, Christoph; Haddadin, Sami; Friess, Helmut; Feussner, Hubertus; Wilhelm, Dirk (SAGE Journals, 2024)
Supplemental material, sj-docx-1-dhj-10.1177_20552076231225084 for Toward telemedical diagnostics—clinical evaluation of a robotic examination system for emergency patients by Maximilian Berlet, Jonas Fuchtmann, Roman Krumpholz, Abdeldjallil Naceri, Daniela Macari, Christoph Jähne-Schon, Sami Haddadin, Helmut Friess, Hubertus Feussner and Dirk Wilhelm in DIGITAL HEALTH ...